Elevated thymidine kinase 1 expression at baseline predicts poor prognosis in breast cancer patients - Li, Peng; Cheng, Yongting; Zhao, Junfeng; Fang, Yuan; Zhao, Tingting (Frontiers in Oncology, 2026)
IntroductionThymidine kinase 1 (TK1), a key enzyme in DNA biosynthesis, has been shown to correlate with breast cancer prognosis and treatment response in dynamic monitoring settings. However, the clinical relevance of baseline TK1 levels remains controversial due to inconsistent evidence across studies. To address this issue, we conducted the first systematic meta-analysis of available studies to investigate the potential association between baseline TK1 levels and prognostic outcomes in breast cancer patients.MethodsA comprehensive computerized literature search was conducted across major Chinese and English databases to identify studies investigating the association between TK1 expression and breast cancer prognosis. Baseline TK1 expression levels and corresponding patient survival data were systematically extracted for meta-analysis.ResultsThe meta-analysis evaluating the association between baseline TK1 expression levels and progression-free survival (PFS) in breast cancer included 2,887 patients from 11 studies. Significant heterogeneity was observed across the included studies (I2 = 87.9%, p = 0.099), which persisted even after subgroup analyses. Therefore, a random-effects model was employed, yielding a pooled hazard ratio (HR) of 1.63 (95% confidence interval [CI]: 1.28–2.10, p = 0.000, Z = 3.88). The meta-analysis evaluating the association between baseline TK1 expression levels and OS in breast cancer included 2,233 patients from six studies. Significant heterogeneity was initially observed (I2 = 72.3%, p = 0.003), which was resolved through subgroup stratification by treatment status (treatment-naive versus recurrent disease). In the treatment-naive subgroup, the HR was 1.30 (95% CI: 1.11–1.52, p = 0.001, Z = 3.26). For the recurrent disease subgroup, the HR was 2.10 (95% CI: 1.74–2.54, p = 0.000, Z = 7.64).ConclusionBreast cancer patients presenting with high baseline TK1 expression are associated with significantly worse prognostic outcomes. Collectively, these findings support the clinical potential of TK1 assessment for prognostic risk stratification and treatment guidance, which merits further verification in large-scale, multicenter clinical trials.